2017
DOI: 10.1186/s12879-017-2764-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute undifferentiated fever in India: a multicentre study of aetiology and diagnostic accuracy

Abstract: BackgroundThe objectives of this study were to determine the proportion of malaria, bacteraemia, scrub typhus, leptospirosis, chikungunya and dengue among hospitalized patients with acute undifferentiated fever in India, and to describe the performance of standard diagnostic methods.MethodsDuring April 2011–November 2012, 1564 patients aged ≥5 years with febrile illness for 2–14 days were consecutively included in an observational study at seven community hospitals in six states in India.Malaria microscopy, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 49 publications
5
79
1
Order By: Relevance
“…Fifteen studies (34.1%) used blood film microscopy to test 10,451 participants for malaria and identified parasitemia in 4,301 (41.2%) (31,32,35,36,38,40,41,43,45,46,(60)(61)(62)(63)(64)(65). Eight studies reported malaria and BSI coinfection (31,32,43,45,(61)(62)(63)65 (62,65).…”
Section: Community-onset Bloodstream Infections Antimicrobial Agents mentioning
confidence: 99%
“…Fifteen studies (34.1%) used blood film microscopy to test 10,451 participants for malaria and identified parasitemia in 4,301 (41.2%) (31,32,35,36,38,40,41,43,45,46,(60)(61)(62)(63)(64)(65). Eight studies reported malaria and BSI coinfection (31,32,43,45,(61)(62)(63)65 (62,65).…”
Section: Community-onset Bloodstream Infections Antimicrobial Agents mentioning
confidence: 99%
“…Malaria, dengue, and chikungunya are the most common coinfections reported from India [17]. Scrub typhus, malaria, dengue fever, and leptospirosis coinfections have been reported from Himachal Pradesh, Uttarakhand, central India, Puducherry, and also from other parts of India [2,[18][19][20][21][22]. The prevalence of coinfections among patients with AUF was 1.39% in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Our study contradicts with the common differential of nonspecific fever as a vector-borne disease like malaria, rickettsia, leptospirosis, and dengue. In a cohort study of 1258 patients in South India, scrub typhus was the most common cause of acute undifferentiated febrile illness (35.9%) followed by dengue (30.6%), malaria (10.4%), enteric fever (3.7%), and leptospirosis (0.6%) [6]. Scrub typhus and dengue were the most common cause of fever in Central India [7].…”
Section: Resultsmentioning
confidence: 99%